A new approach to improvement of yam (Dioscorea rotundata) - Sadik, S.; Okerere, O.U. (Springer, 1975)
EFFORTS to improve the yam, D. rotundata, through hybridisation have been frustrated by the low rate of flowering, the very low rate of fruit setting and poor seed germination1–3. These constraints have confined the availability of genetic resources for selection to the small number of cultivars which have been vegetatively reproduced from time immemorial. This continued vegetative propagation and the lack of hybridisation have precluded the possibility of introduction of new genetic characteristics, resulting in a stagnation of yam improvement. To facilitate yam hybridisation, we have re-examined the problems of flowering and seed germination. We first reported4 yam seed germination in November 1973, and Doku stated that he had germinated yam seeds of D. rotundata (unpublished). Here we report the feasibility of germinating yam seeds, the rapid improvement of flowering, and the opportunity this development affords for expanding present germ plasm collections, thus facilitating yam improvement.